2006
DOI: 10.1007/s00330-005-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Image-guided percutaneous biopsy of intramedullary lytic bone lesions: utility of aspirated blood clots

Abstract: The diagnostic value of aspirating blood clots while performing percutaneous biopsy of intramedullary lytic bone lesions was assessed. This was a retrospective analysis of 400 patients with intramedullary lytic bone lesions who underwent image-guided needle biopsy. The nature of the specimens obtained was noted from the histopathology records. In 83 (20.8%) of the 400 patients, the specimen obtained was either blood clot only or essentially blood clot with only tiny fragments of bone or soft tissue. Lesional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
(35 reference statements)
1
5
0
Order By: Relevance
“…even in patients with a known primary tumor and suspicious bone lesion, whose chance of a diagnosis different from metastasis is low, the confirmation of the diagnosis is required because it can influence these patients' management and prognosis, especially for the patients with breast cancer. This study's results have demonstrated that 77.6% of CT-guided bone lesion biopsy specimens were sufficient for histopathological analysis, which is in concordance with the reported rate of successful percutaneous bone biopsies of musculoskeletal lesion ranging from 69 to 93% (5)(6)(7)(8)(9)(10).…”
Section: Figure 1 Ct-guided Percutaneous Bone Biopsy A: Planning Pelvic Ct With the Grid (Star) Demonstrates A Lytic Lesion In The Left Isupporting
confidence: 87%
See 1 more Smart Citation
“…even in patients with a known primary tumor and suspicious bone lesion, whose chance of a diagnosis different from metastasis is low, the confirmation of the diagnosis is required because it can influence these patients' management and prognosis, especially for the patients with breast cancer. This study's results have demonstrated that 77.6% of CT-guided bone lesion biopsy specimens were sufficient for histopathological analysis, which is in concordance with the reported rate of successful percutaneous bone biopsies of musculoskeletal lesion ranging from 69 to 93% (5)(6)(7)(8)(9)(10).…”
Section: Figure 1 Ct-guided Percutaneous Bone Biopsy A: Planning Pelvic Ct With the Grid (Star) Demonstrates A Lytic Lesion In The Left Isupporting
confidence: 87%
“…The rate of successful percutaneous bone biopsies of the musculoskeletal lesion is 69 -93% in the literature. (5)(6)(7)(8)(9)(10). The rate of complications in CT-guided bone biopsies is very low (1.1%), while in surgical (open) biopsies, it may be as high as 16% (11).…”
Section: Introductionmentioning
confidence: 99%
“…21 In their series and others, the (3) Nonspesific osteomyelitis (2) Tuberculous osteomyelitis (1) Tuberculous osteomyelitis (2) Tuberculous osteomyelitis (2) Hematoma (2) Nonspesific osteomyelitis (1) Lymphoma (1) Inadequate (1) Tuberculous osteomyelitis (1) Normal (10) Normal (8) Normal (2) Nonspesific osteomyelitis (2) Tuberculous osteomyelitis (2) Metastatic tumor (1) Hemangioma (1) Nonspesific osteomyelitis (2) Nonspesific osteomyelitis (2) Tuberculous osteomyelitis (3) Tuberculous osteomyelitis (3) Tuberculous osteomyelitis (3) Plasmacytoma (4) Plasmacytoma (4) Plasmacytoma (4) Lymphoma (2) Lymphoma (2) Lymphoma (2) Chordoma or chondrosarcoma (2) Chordoma (1) Chordoma (1) Chondrosarcoma (1) Chondrosarcoma (1) Sarcoma (1) Osteosarcoma (1) Osteosarcoma (1) PNET or lymphoma (1) PNET/Ewing sarcoma (1) PNET/Ewing sarcoma (1) Inadequate (15) Nonspesific osteomyelitis (6) Nonspesific osteomyelitis (6) Plasmacytoma (3) Plasmacytoma (3) Lymphoma (2) Lymphoma (2) Tuberculous osteomyelitis (1) Tuberculous osteomyelitis (1) Lymphoma/plasmacytoma (1) Plasmacytoma (1) Inadequate (2) Plasmacytoma (1) Metastatic tumor (1) osseous blood showed better malignant tissue morphology and was considered better diagnostic material than bone cores. [21][22][23] Some authors, however, were against this suggestion (use of osseous blood) and proposed that such tissue is of little or no diagnostic value. 24,25 Dupuy et al recommended the use of core needle biopsy with frozen section analysis or rapid cytological interpretation from touch preparation in spinal or pelvic lesions in which a small round cell lesion is in the differential diagnosis.…”
Section: Discussionmentioning
confidence: 94%
“…13 14 In addition, aspirated blood clots should be considered as a tissue specimen because they have been shown to increase the diagnostic yield. 15…”
Section: Percutaneous Biopsymentioning
confidence: 99%